2009 International Conference on Computer Engineering &Amp; Systems 2009
DOI: 10.1109/icces.2009.5383290
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification techniques of galaxies using artificial neural networks based classifiers

Abstract: Processing and classifying galaxy information is one of the most important challenges and intensive research area for astronomers. In this paper; analyzing and classifying photographic images of galaxies are presented, with interesting scientific findings gleaned from the processed photographic data. In addition, the performance of ten artificial neural networks (ANNs) based classifiers was evaluated, based on a selected set of features. They are a combination of a set of morphic features; derived from image a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Galaxies show a vast range of forms, Astronomers for many decades have been trying to find the underlying order in the diverse properties of galaxies [6]. They have found that galaxies can be categorized based on their physical appearances.…”
Section: Galaxy Morphological Classification 21 Hubble's Classificatmentioning
confidence: 99%
See 3 more Smart Citations
“…Galaxies show a vast range of forms, Astronomers for many decades have been trying to find the underlying order in the diverse properties of galaxies [6]. They have found that galaxies can be categorized based on their physical appearances.…”
Section: Galaxy Morphological Classification 21 Hubble's Classificatmentioning
confidence: 99%
“…They have found that galaxies can be categorized based on their physical appearances. One of the most common classification schemes is the system devised by Sir Edwin Hubble in 1936, It is often known as the "Hubble tuning-fork", Hubble"s scheme divides galaxies into three classes based on their visual appearance: (i) Elliptical; (ii)Spiral; (iii) Barred spiral; and (iv)Irregular [6]. As shown in figure (1).…”
Section: Galaxy Morphological Classification 21 Hubble's Classificatmentioning
confidence: 99%
See 2 more Smart Citations